Provenance Trial of Eucalyptus tereticornis in Punjab - Kapur, S. K.; Dogra, A. S. (Indian Forester, 1987)
Provenance trial of Eucalyptus tereticornis Sm. Was undertaken in Ferozepur Forest Division, Punjab in August, 1982. A randomised line design with 20 treatmeats in all Including tth control was adopted for the trial. The analysis of data collected 3.5 years after the planting showed that Lekeland downs and Kennedy river.34 km N of Laura provenances of E. tereticornis, which did not significantly differ in their performance from each other were significantly superior to all other provenance in terms of volume production.